Optimizing the primary stability of dental implants in type IV bone: in-vitro comparison of machine-driven and ratcheting insertion protocols - Taysi, Nuri Mert; Taysi, Aysegul Erten; Ercal, Pinar; Sismanoglu, Soner (Istanbul Univ Press, Istanbul Univ Rectorate, 2025)
Purpose The objective of this study was to assess the effects of various implant insertion techniques on the primary stability of dental implants in both type II and type IV cadaveric bovine. Materials and Methods A total of 48 dental implants (BEGO Semados RSX, BEGO Implant Systems GmbH & Co. KG, Germany) with a diameter of 3.75 mm and a length of 12 mm were used in the experiments. Bovine bone ribs were adjusted to mimic type II and type IV bone characteristics. Following the preparation of recipient sites, implants were inserted using three different protocols: machine-driven insertion (Standard group, Std group), ratchet insertion (Ratcheted, R Group), and a combination of both (Std + R group).The Osstell (R) Beacon device was used to record the implant stability quotient (ISQ) of each implant immediately after insertion. Two-way analysis of variance and Bonferroni tests were used for statistical evaluation. Results Bone type significantly influenced the ISQ values (p<0.05). However, when comparing insertion protocols separately for type II and type IV bone, no significant differences were observed. In type IV bone, both the Std group and R group exhibited significantly lower ISQ values compared to the same groups in type II bone (p<0.05 for each). Nevertheless, there were no significant differences in the ISQ values when employing the Std+R technique between the two types of bone. Conclusion Combining machine-driven and ratchet insertion techniques may prove beneficial in optimizing ISQ values in bovine samples simulating type IV bone.
Keywords: Dental implants; oral surgical procedures; osseointegration; resonance frequency analysis